Translation and validation of the Cancer-Related Fatigue Scale in Greek in a sample of patients with advanced prostate cancer - Charalambous, Andreas; Kaite, Charis P.; Constantinou, Marianna; Kouta, Christiana (My University, 2016)
To translate and validate the Cancer-Related Fatigue (CRF) Scale in the Greek language.
Keywords: CHEMOTHERAPY; Fatigue; Neoplasms; Severe fatigue